1995
DOI: 10.1288/00005537-199504000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A comparative diagnostic study of head and neck nodal metastases using positron emission tomography

Abstract: A prospective study was conducted to compare the accuracy of clinical examination, computed tomography (CT), and positron emission tomography (PET) in identifying head and neck squamous cell carcinoma metastatic to cervical lymph nodes. The findings in the necks of 49 patients evaluated by clinical examination and CT were compared to the findings in the same necks by PET, a newly available metabolic imaging modality. Pathology specimens were available for 45 of the necks. The findings of PET and CT correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(65 citation statements)
references
References 7 publications
3
57
0
5
Order By: Relevance
“…Since PET studies indicate the metabolic changes, it provides information about the lesion earlier than the other imaging methods and PET-CT studies contribute to the early diagnosis and correct staging of the disease due to the fact that anatomical localization and details are indicated with CT (14). In many studies conducted to determine lymph node metastasis, PET-CT has been found to have higher sensitivity (64%-100%) and specifity (67%-100%) and a more frequently preferred method when compared to MRI and CT (15,16 Liao et al's (19) study including 473 patients, when SUV-max threshold value is taken as 3.1, sensitivity and specifity were found 79.9% and 59.4% respectively. In our study when the threshold value is taken as 2.5 in detection of the metastatic region in the neck, sensitivity, specifity, PPD and NPD and accuracy were found 73%, 91%, 40.7%, 96.6% and 86% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Since PET studies indicate the metabolic changes, it provides information about the lesion earlier than the other imaging methods and PET-CT studies contribute to the early diagnosis and correct staging of the disease due to the fact that anatomical localization and details are indicated with CT (14). In many studies conducted to determine lymph node metastasis, PET-CT has been found to have higher sensitivity (64%-100%) and specifity (67%-100%) and a more frequently preferred method when compared to MRI and CT (15,16 Liao et al's (19) study including 473 patients, when SUV-max threshold value is taken as 3.1, sensitivity and specifity were found 79.9% and 59.4% respectively. In our study when the threshold value is taken as 2.5 in detection of the metastatic region in the neck, sensitivity, specifity, PPD and NPD and accuracy were found 73%, 91%, 40.7%, 96.6% and 86% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The most important reason that PET/CT is a preferred method over others for contouring target volumes is that it can provide better differentiation of tumor tissue from healthy tissue (McGuirt et al, 1995). Comparing target tumor volumes determined by CT and PET/CT images may result in changing the treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…Although validation of sites of malignancy was not part of this trial design, the accuracy of PET in staging head and neck cancer has been extensively reported in the literature (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)23). Information from referring clinicians as well as from radiology and PET reports was used for lesion evaluation, and no centralized review of the imaging was made.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the use of PET in the initial staging of head and neck cancer (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). 18 F-FDG PET may offer advantages over anatomic imaging in the assessment of primary tumors, as it can detect superficial or submucosal primary tumor infiltration without adjacent tissue deformation, and nodal disease (1,2).…”
mentioning
confidence: 99%